2018
DOI: 10.1371/journal.pone.0196114
|View full text |Cite
|
Sign up to set email alerts
|

Effect of post-discharge virtual wards on improving outcomes in heart failure and non-heart failure populations: A systematic review and meta-analysis

Abstract: BackgroundUnplanned hospital admissions in high-risk patients are common and costly in an increasingly frail chronic disease population. Virtual Wards (VW) are an emerging concept to improve outcomes in these patients.PurposeTo evaluate the effect of post-discharge VWs, as an alternative to usual community based care, on hospital readmissions and mortality among heart failure and non-heart failure populations.Data sourcesOvid MEDLINE, EMBASE, PubMed, the Cochrane Database of Systematic Reviews, SCOPUS and CINA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 37 publications
(42 reference statements)
5
40
0
1
Order By: Relevance
“…Previous systematic reviews have found that interventions including patient education, home visits, self-management support, and telemonitoring have been effective in reducing hospital readmissions [ 48 52 ]. As such, these findings support those reported in our previous work [ 8 ] and are broadly consistent with recent systematic reviews in heart failure [ 49 52 ]. Thus, there appears to be strong evidence for efficacy of post-discharge interventions in heart failure patients.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Previous systematic reviews have found that interventions including patient education, home visits, self-management support, and telemonitoring have been effective in reducing hospital readmissions [ 48 52 ]. As such, these findings support those reported in our previous work [ 8 ] and are broadly consistent with recent systematic reviews in heart failure [ 49 52 ]. Thus, there appears to be strong evidence for efficacy of post-discharge interventions in heart failure patients.…”
Section: Discussionsupporting
confidence: 93%
“…A variety of post-discharge interventions have been proposed to reduce this readmission risk, ranging from minimal (i.e. follow-up telephone calls), to complex, multifaceted interventions such as “virtual wards”, which provide patients with a period of intensive multidisciplinary team management, often employing telemonitoring and nurse led case-management strategies [ 8 ]. Use of virtual wards following hospital discharge has been associated with a lower risk of readmission in certain health conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, drawing an analogy between telemonitoring and nurse-led case management is also reasonable, because most telemonitoring interventions apply principles or components of case management delivered remotely. 13 Our model has several important implications for the future development of home monitoring technologies in CKD. First, the economics appear to be very favorable, as even a small effect could allow for a reasonable intervention cost to generate substantial cost savings for the health care payer.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, telemonitoring and virtual ward technologies (virtual case management) have shown benefit in highrisk, specific disease states such as heart failure. 13 It is tempting to hypothesize that enhanced monitoring of patients with late-stage CKD using this technology may reduce the rate of suboptimal dialysis starts; however, the costs of any such intervention must be weighed against the potential benefits.…”
mentioning
confidence: 99%
“…Additionally, virtual ward rounds may become a routine part of NHS service for post-operative patient follow up. A recent systematic review 10 has demonstrated that patients with heart failure, have reduced rates of re-admission and mortality with post-discharge ward rounds than with standard community-based care. Hence not only may virtual clinical encounters prove educationally beneficial, but they may also be more representative of the future health service.…”
Section: Virtual Reality and Augmented Realitymentioning
confidence: 99%